Dynamics of a 'flying chimney'. (21st November 2016) - Ji, Runda; Sandali, Yahya; Zhu, Changqing; Coileáin, Cormac Ó; Shi, Qingfan
Abstract: The 'flying chimney', where a paper cylinder floats when set alight, is an interesting phenomenon that lacks both systematic theoretical and experimental investigation. To investigate the dynamics of liftoff, an appropriate chimney material was first selected from 22 kinds of traditional Chinese Xuan paper. Subsequent experiments with this paper, examining the relationship between the likelihood of liftoff and the height of the air-gap under the cylinder, show the necessity of a gap and the ideal minimum height required to assure successful liftoff. We experimentally investigate the cylinder geometry, determining the optimal parameters for height and diameter, and the boundary conditions for which liftoff can occur. In order to reveal the mechanism of liftoff, a physical model in which the viscous force is reasonably suggested to be a key kinetic parameter is proposed. The viscous force can be obtained by substituting the velocity field of heated air-flow into the constitutive equations of a Newtonian fluid. Numerical calculation for the size effect of liftoff is in good agreement with the experimental data.